Constraining the Milky Way halo potential with the GD-1 stellar stream. Issue 3 (13th April 2019) - Malhan, Khyati; Ibata, Rodrigo A
Abstract: We use ESA/ Gaia astrometry together with SEGUE and LAMOST measurements of the GD-1 stellar stream to explore the improvement on the Galactic gravitational potential that these new data provide. Assuming a realistic universal model for the dark matter halo together with reasonable models of the baryonic components, we find that the orbital solutions for GD-1 require the circular velocity at the Solar radius to be $V_{\rm circ}({\rm R}_\odot) =244± 4{\rm \, km\, s^{-1}}$, and also that the density flattening of the dark halo is $q_{ρ }=0.82^{+0.25}_{-0.13}$ . The corresponding Galactic mass within $20{\rm \, kpc}$ was estimated to be $M_{\rm MW}(\lt 20{\rm \, kpc})=2.5± 0.2 × 10^{11} {\rm \, M_\odot }$ . Moreover, Gaia 's excellent proper motions also allowed us to constrain the velocity dispersion of the GD-1 stream in the direction tangential to the line of sight to be $\lt 2.30{\rm \, km\, s^{-1}}$ (95 per cent confidence limit), confirming the extremely cold dynamical nature of this system.